Selection of Payloads for Antibody–Drug Conjugates Targeting Ubiquitously Expressed Tumor-Associated Antigens: a Case Study - Yao, Bing; Gao, Xiao; Dan, Mo; Yuan, Can; Hu, Xixin; Sun, Zhaopeng; Hui, Xiwu; Liu, Boning; Ouyang, Pingkai; Chen, Guoguang (The AAPS journal, 2022)
The main objective of this work was to demonstrate which kind of payload is the suitable choice for antibody–drug conjugates directed to widely expressed tumor-associated antigen. Trop-2 is overexpressed in various solid tumors, but it is also present on the epithelium of several normal tissues. A well-designed anti-Trop-2 ADC demands a good balance of efficacy and toxicity. In this research, MMAE, SN-38, and DXd were selected as candidates for payloads of the anti-Trop-2 mAb SY02. The antitumor activities and safety profiles of these ADCs were investigated to compare the therapeutic windows. Robust in vitro cytotoxicity was observed on human pancreatic cancer cell CFPAC-1 and breast cancer cell MDA-MB-468 with IC 50 generally in the subnanomolar range. Consistent with in vitro assay, SY02-DXd and SY02-SN-38 demonstrated superior efficacy in CFPAC-1 xenograft models with TGI rates of 98.2% and 87.3%, respectively. However, SY02-MMAE could hardly inhibit the tumor growth. Subsequently, antitumor activities of these ADCs were further compared in MDA-MB-468 xenograft model. Complete tumor regression was observed in SY02-DXd and SY02-MMAE groups, indicating their potent antitumor activities. In an exploratory safety and pharmacokinetic study, SY02-DXd demonstrated the best safety profile with minimal adverse events in cynomolgus monkeys, while SY02-MMAE exhibited severe on-target skin toxicity which caused death. In conclusion, SY02-DXd demonstrated superior efficacy and safety with the widest therapeutic window. Based on the efficacy and safety results, moderate cytotoxic payloads would be ideal choices for ADCs targeting ubiquitously expressed antigens. Graphical Abstract